Effect of EAP Psychological Intervention on Improving the Mental Health of Medical Workers Under the Novel Coronavirus Epidemic in China - Xu, Jun; Liu, Xia; Xiao, Yundan; Fang, Xiaohui; Cheng, Yingsheng; Zhang, Jinping (Frontiers in Public Health, 2021)
Background: Due to the novel coronavirus epidemic, medical workers are under immense psychological pressure. As such, the East Campus of Shanghai Sixth People's Hospital actively adopted the Symptoms Checklist 90 (SCL-90) to evaluate the mental health of hospital staff before and after the psychological intervention from the Employee Assistance Program (EAP). Methods: Medical workers from the East Campus of Shanghai Sixth People's Hospital were recruited for this study. Psychological evaluations were conducted using the SCL-90, with a score of >160 regarded as a positive result, or in other words, an indication of abnormal psychological symptoms. The EAP adopted different forms of psychological interventions for healthcare professionals, and participation in these measures was entirely voluntary. Medical workers completed the SCL-90 again after participating in the psychological intervention, and we analyzed the changes between their two assessments. Results: Of the 1,198 total medical staff present at the hospital, 844 participated in the initial survey, while only 652 completed the survey a second time (i.e., post-psychological intervention). Multivariate logistic regression analysis found that the psychological status of hospital staff was correlated with gender, education background, and fertility status (P < 0.05). The results showed that, compared with women, men's mental health status was better, with an OR value of 0.598 (0.372–0.962). Groups with high school, junior high school, and below education levels were at higher risk of psychological problems, with OR values of 23.655 (2.815–198.784) and 9.09 (2.601–31.801), respectively. Administrative occupations and having two or more children were protective factors for mental health, and the OR values were 0.400 (0.175–0.912) and 0.327 (0.152–0.703), respectively. Following the psychological intervention, we found that the mental health of hospital workers improved, as indicated by their second SCL-90 evaluations, although the proportion of medical staff willing to participate in the second evaluation was lower than the initial assessment. There were differences in the SCL-90 scores among different occupations, and there were also differences in the scores of employees of different occupations who had participated in the two evaluations. The employees of different positions who participated in the two evaluations were matched and analyzed and found that the depression and anxiety of the doctor group were significantly reduced. In the nursing group, the total score, somatization, interpersonal sensitivity, depression, and anxiety were significantly reduced. In the medical technician group, depression, anxiety, and paranoia were reduced considerably. Among office staff, no significant differences were found. Among workers, the total score, depression, and anxiety were significantly reduced. Conclusion: Hospitals have the potential to alleviate and reduce the psychological pressure placed on medical staff members through the EAP, which can actively adopt intervention and guidance measures. The findings of this study have important implications, as reducing abnormal psychological symptoms of healthcare professionals can be helpful in the fight against the coronavirus epidemic.